Short biceps femoris fascicles and eccentric knee flexor weakness increase the risk of hamstring injury in elite football (soccer): a prospective cohort study - Timmins, R. G.; Bourne, M. N.; Shield, A. J. (British Journal of Sports Medicine, 2016)
Background/aim: To investigate the role of eccentric knee flexor strength, between-limb imbalance and biceps femoris long head (BFlh) fascicle length on the risk of future hamstring strain injury (HSI).